Theorems for Boyd-Wong-Type Contractions in Ordered Metric Spaces. (29th September 2012) - Aydi, Hassen; Shatanawi, Wasfi; Postolache, Mihai; Mustafa, Zead; Tahat, Nedal
Abstract : We give some fixed point results using an ICS mapping and involving Boyd-Wong-type contractions in partially ordered metric spaces. Our results generalize, extend, and unify several well-known comparable theorems in the literature. Also, we present some examples to support our results.